Profil Siswa Agresif Dan Peranan Guru BK - Hidayat, Hafiz; Yusri, Yusri; Ilyas, Asmidir (Universitas Negeri Padang, 2015)
Teenshave apositiveandnegativebehavior. Negativebehavioris notcharacteristicof normaladolescent development, adolescentsaredeveloping willexhibitpositivebehavior. One of theteensindicatednegativebehaviorisaggressivebehavior. It can be seeninSMAN5Padangisquarrelsome, liketeasing,hitting, pinchingher, sayingrude, insulting. This studyaimed to describe thetype ofaggressivebehaviorof studentsandthe role ofBKteachersto addressstudents'aggressivebehaviorSMAN5Padang. This studyused a descriptive approach. The study populationwas ahigh school studentPadangN5340peoplewith atotalsampleamounted to 77people. Questionnairedata collection techniquesto use. Datawere analyzed usingMicrosoftOfficeExcel 2007. The findingsshowed thatstudents'views of theaggressiveactionshurt peoplephysicallywith apercentage of35.32%, while theaggressiveactionsof the studentviewsofhurtingpeopleverbally41.30% and aggressionseenfromdamaginganddestroyingpropertyby30percent, 42%. Thismeans thatthe presence ofaggressivebehaviorinSMAN5Padang.Â